Source tracing analysis of the exceedance of NH3-N and CODMn in shallow groundwater in the central typical area of the Yangtze river delta - Xiangmei Li; Kexin Li; Shuqin Li; Zehai Li; Lili Wan; Wei Guo (Scientific Reports)
Abstract With the accelerated urbanization process in the Yangtze River Delta region, shallow groundwater has received increasing attention. In this work, the exceedances of the ammonium nitrogen (NH3-N) and chemical oxygen demand (CODMn) in shallow groundwater in the central typical area of the Yangtze River Delta were investigated. With the utilization of the national monitoring well (QY10A) as a focal point, a combination of methods, including onsite sampling, hydrogeological surveys, leaching tests, water quality analysis, and isotope tracing, was employed to comprehensively examine groundwater pollution. The study addressed the history of groundwater exploitation, changes in surface water quality, and the influence of stratigraphic structure on groundwater contamination. It has been observed that the NH3-N levels in the silty chalky clay layer and the lower grayish black chalky clay layer in the study area are notably elevated, with concentrations reaching up to 87.5 mg/kg and 97.4 mg/kg in some boreholes. The NH3-N concentration in the silty clay with silty sand can reach as high as 87.2 mg/kg, whereas the concentration is lower in the underlying layers. In the other strata, NH3-N values remain low. The results indicated that the NH3-N and CODMn in the QY10A monitoring well resulted primarily from the inherently high organic nitrogen content in the local geological environment rather than from anthropogenic sources such as industrial parks, domestic sewage, or agricultural activities. This finding highlights the critical role of geological conditions in influencing groundwater quality, emphasizing the necessity of considering these natural factors in pollution prevention and management strategies. Our research provides valuable insights for environmental management in similar geological settings and demonstrates the importance of scientifically rigorous methods for advancing environmental research and policy-making.